Extension at the coast of the Makran subduction zone (Iran). (30th July 2019) - Normand, Raphaël; Simpson, Guy; Bahroudi, Abbas
Abstract: In the Makran subduction zone, earthquake focal mechanisms and geodetic data indicate that the deforming prism currently experiences N–S compression. However, palaeostress inversions performed on normal faults observed along the coast reveal local stress components consistent with N‐S extension. Previously proposed mechanisms such as gravitational collapse are not favoured by N–S compression and surface uplift. We propose that the observed kinematics result from transient stress reversals following large earthquakes. During the interseismic period (now), the region experiences N–S compression. However, following a large reverse rupture on the subduction interface, stresses in the inner wedge relax, enabling a brief period of extensional faulting before a compressive stress state is re‐established. This mechanism, also observed in other subduction zones, requires low overall stresses in the upper plate and that the margin ruptures in large megathrust earthquakes that result in nearly complete stress drops.